(untitled) (Revista de Investigaciones Universidad del Quindío, 2011)
Acid hydrolysis is a pretreatment method used in order to enhance biomass accessibility to enzymatic hydrolysis towards ethanol production. For that reason, some chemical changes in biomass from Cavendish Valery banana rachis by acid hydrolysis were researched. Using the combined severity (CS) that takes into account temperature, time and pH; how the change in the content of cellulose, holocellulose, hemicelulose, reducing sugars and 5hydroxymthylfurfural (HMF) was observed. Results suggest that when CS=2,67 (170 ºC, 40 min y 1% de sulfuric acid), the sample showed a maximum sugar content versus low HMF formation. Additionally, hemicelluloses degradation was established meanwhile cellulose degradation was not evident.